Comprehensive Review of Role Integration between Nurses and Nurse Assistants: Bridging Gaps in Patient Care through Collaborative Practices - Lsloom , Nasser Abdullah M; Humayyim , Fahad Ali M Bani; Alsallum, Mohammed Abdullah M; Al Hamry , Salem Awad N; Al-Saloum , Ayed Mahdi N; Alanazi, Shikha Khalid M; Alruwili , Salem Mutlaq S; Alazmi , Tahani Mubarak M; Alanizi , Maha Fahad; Albalawiy , Fawzah Halil; Alazmi , Zainab Hamdan S; Al Anizy , Delayel Tayar; et al. (Journal of Ecohumanism, 2024)
The interpersonal relations between the nurses and the nurse assistants are very important for overall patient care delivery. This paper aims to analyses the interaction of those professions to elucidate current problems and possible improvements in their interaction. Conducting a multiple-source analysis of the current literature, survey, and case studies, we offer practical recommendations. Issues of communication, role definition issues, and the effect of teamwork on patients are some of the important findings of the study. Suggestions for addressing the gaps are improved training processes, rail implementation, and promotion of respect between the two categories.